Cephalexin-mediated synthesis of quasi-spherical and anisotropic gold nanoparticles and their in situ capping by the antibiotic - Jagannathan, Ramya; Poddar, Pankaj; Prabhune, Asmita (Journal of Physical Chemistry C, 2007)
Here we report, for the first time, synthesis of gold nanostructures in aqueous medium by reducing gold ions using cephalexin, a potent broad-spectrum antibiotic, where the morphology of the gold nanoparticles is found to be dependent on the concentration of chloroauric acid. The characterization techniques indicate that particle surfaces are coated with the robust layer of the antibiotic making them stable for a long time. Thus, cephalexin acts as both the reducing and the capping agent. NMR and XPS analysis indicate that the sulfur moiety is responsible for the reduction and binding process.

Challenges associated with metal chelation therapy in alzheimer's disease - Hegde, Muralidhar L.; Bharathi, P.; Suram, Anitha; Venugopal, Chitra; Jagannathan, Ramya; Poddar, Pankaj; Srinivas, Pullabhatla; Sambamurti, Kumar; Rao, Kosagisharaf Jagannatha; Scancar, Janez; Messori, Luigi; Zecca, Luigi; et al. (Journal of Alzheimers Disease, 2009)
A close association between brain metal dishomeostasis and the onset and/or progression of Alzheimer's disease ( AD) has been clearly established in a number of studies, although the underlying biochemical mechanisms remain obscure. This observation renders chelation therapy an attractive pharmacological option for the treatment of this disease. However, a number of requirements must be fulfilled in order to adapt chelation therapy to AD so that the term ``metal targeted strategies'' seems now more appropriate. Indeed, brain metal redistribution rather than brain metal scavenging and removal is the major goal of this type of intervention. The most recent developments in metal targeted strategies for AD will be discussed using, as useful examples, clioquinol, curcumin, and epigallocatechin, and the future perspectives will also be outlined.
Keywords: Alzheimer's disease; clioquinol; cuprizone; metal dishomeostasis; metal ions; nanomedicine; Parkinson's disease; polyphenols

In situ observation of antibiotic mediated concurrent growth of two distinct homogeneous populations of gold nanoparticles in solution phase - Jagannathan, Ramya; Parmar, Avanish Singh; Adyanthaya, Suguna D.; Prabhune, Asmita; Muschol, Martin; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
We report the observation of the unusual nucleation and growth kinetics of gold nanoparticles synthesized in the presence of the antibiotic cephalexin using in situ static and dynamic light scattering in conjunction with in situ UV-vis absorption measurements and transmission electron microscopy. Following a brief latency period, two well-separated populations of gold nanoparticles, with average sizes of 1-2 nm versus several tens of nanometer, respectively, nucleate simultaneously. For either size regime, the total number of particles increased rapidly, while their mean size and relative frequency remained essentially constant over a growth period of 5 h. With increasing temperature, the morphology of the larger nanoparticles became increasingly spherical, as indicated by the noticeable blue shift of the plasmon frequency for these particles. The detailed morphology for either particle population was confirmed with TEM. To our knowledge, this is the first observation of simultaneous growth of two distinct populations of crystalline nanoparticles in the solution phase. The coupled growth of two distinct populations of nuclei, their tight control of size but rapid increase in overall numbers present novel and intriguing facets of this antibiotic-mediated solution-growth of gold nanoparticles. The size evolution of the Mie-frequency exhibits a noticeable blue shift as the temperature increases, correlating with the roundness of the particle/bimodal distribution.

Mechanistic study of surface functionalization of enzyme lysozyme synthesized Ag and Au nanoparticles using surface enhanced raman spectroscopy - Das, Raja; Jagannathan, Ramya; Sharan, Chandrashekhar; Kumar, Umesh; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
The fate of bioactivity of biomolecules such as enzymes, proteins, and even drug molecules is greatly affected by the conformational changes in the proximity of the solid surfaces. This interaction is the key to the potential of their further applications as biosensors, in drug delivery, etc. With increasing interest in the biofunctionalization of noble metal nanoparticles for various applications, it is important to precisely investigate the functional groups responsible for binding with the nanoparticle surfaces and probable structural changes in the structure of the biomolecules as both are key factors affecting the bioactivity of these molecules once they are tagged onto the nanoparticle surfaces. However, it is not an easy task to probe these properties, especially for bigger Molecules such as enzymes and proteins. Surface-enhanced Raman spectroscopy (SERS) has been used extensively in the detection of biomolecules and study of their conformation on noble metal surfaces since its discovery because of its high sensitivity. This technique is capable of detecting changes in the secondary structure and the effects of surrounding environment on the biomolecule in the proximity of nanoscopic rough metal surfaces. In this study, we have used this technique to precisely determine the functional groups responsible in the Surface capping of Ag and Au nanoparticles synthesized by the hen egg derived enzyme lysozyme. The sharp and intense Stokes Raman shift peaks observed around 704, 866, 1519, and 1598 cm(-1), in the case of Ag nanoparticles, which are assigned to tryptophan, tyrosine, phenylalanine, and histidine residues, clearly indicate the involvement of these residues for surface passivation of the Ag nanoparticle surface. The Ag-N peak situated around 236 cm(-1) was also seen in the spectra, showing that probably the amine group of lysozyme is responsible in binding to the Ag nanoparticle surface. Similarly, in the case of Au nanoparticles, we observed sharp and intense peaks around 1583, 1545, and 1584 cm(-1) which were assigned to above-mentioned amino acid residues, indicating that a similar mechanism is also responsible for the binding of lysozyme molecules at the Au nanoparticle surface. In both cases peaks for the amide III band (C-N-H) around 1250 cm(-1) were also observed.

Temperature-dependent spectroscopic evidences of curcumin in aqueous medium: a mechanistic study of its solubility and stability - Jagannathan, Ramya; Abraham, Priya Mary; Poddar, Pankaj (Journal of Physical Chemistry B, 2012)
In curcumin, keto-enol-enolate equilibrium of the heptadiene-dione moiety determines its physiochemical and antioxidant properties. However, its poor solubility in water at neutral pH and room temperature decreases its bioavailability. Potential therapeutic applications have triggered an interest in manipulating the solubility of curcumin in water as its stability and solubility in water remains poorly understood. Here, the mechanism behind its solubility at various temperatures and the influence of interplay of temperature, intramolecular H-bonding, and intermolecular forces is reported, which leads to aggregation-disaggregation at various temperatures. Remarkable change is observed in temperature-dependent electronic transition behavior of curcumin, however, the absorption spectra after cooling and heating cycles remain unchanged, hinting much better thermal stability of curcumin in water than previously thought. This study indicates that it is perhaps the breaking of intramolecular hydrogen bonding which leads to exposure of polar groups and hence responsible for the dissolution of curcumin at higher temperature. The formation of intermolecular aggregates might be responsible behind a better room temperature stability of the molecules after cooling its aqueous suspension from 90 to 25 degrees C. These curcumin solubility studies have great application in biological research with reference to bioavailability and to understand target oriented mode of action of curcumin.

In situ synthesis and surface functionalization of gold nanoparticles with curcumin and their antioxidant properties: an experimental and density functional theory investigation - Singh, Dheeraj K.; Jagannathan, Ramya; Khandelwal, Puneet; Abraham, Priya Mary; Poddar, Pankaj (Nanoscale, 2013)
Curcumin ((1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) is an active component of turmeric; it is responsible for its characteristic yellow color and therapeutic potential, but its poor bioavailability remains a major challenge. In order to improve the bioavailability of curcumin, various approaches have been used. One of the possible approaches to increase the bioavailability of curcumin is its conjugation on the surface of metal nanoparticles. Therefore, in the present study, we report the binding of curcumin on the surface of gold nanoparticles (AuNPs). The AuNPs were synthesized by the direct reduction of HAuCl4 using curcumin in the aqueous phase, without the use of any other reducing agents. We found that curcumin acts both as a reducing and capping agent, stabilizing the gold sol for many months. Moreover, these curcumin-capped AuNPs also show good antioxidant activity which was confirmed by the DPPH (2,2-diphenyl-l-picrylhydrazyl) radical test. Thus, the surface functionalization of AuNPs with curcumin may pave a new way of using the curcuminoids towards possible drug delivery and therapeutics. Apart from the experimental study, a detailed quantum chemical calculation using density functional theory (DFT) has been performed, in order to investigate the formation of a complex of curcumin with Au3+ ions in different possible conformational isomeric forms. Our theoretical calculations indicate the evidence of electron transfer from curcumin into the Au center and essentially indicate that as a consequence of complexation, Au3+ ions are reduced to Au-0. Our theoretical results also propose that it is the breakage of intramolecular H-bonding that probably leads to the increased availability of curcumin in the presence of gold ions and water molecules.